Correction of microbiocenosis of female reproductive tract during the late stage of pregnancy - O P Lebedeva (RUDN Journal of Medicine, 2012)
Pobedi str., 85, Belgorod, Russia, 308024 Bacteriological examination of cervical canal at 34 women in 38—40 weeks of gestation has been made before and after intravaginal usage of Gynoflor (“Medinova”, Switzerland), containing 50 mg of Lactobacillus acidophilius and 0,03 mg of estriol. It is established, that after usage of Gynoflor significant decrease of number of patients with Staphylococcus epidermidis and Peptococcus has been observed. Furthermore, lowering of number of women with other opportunistic bacteria and yeasts ( Staphylococcus aureus , Klebsiella pneumonia , Enterococcus , Enterobacter , Streptococcus , Bacteroides , Candida albicans ) has been appeared. It was accompanied with decrease of colony forming units number among all opportunistic species.